(untitled) (Journal of Social Sciences Review, 2023)
India and Pakistan have been colonized at different times, but Afghanistan has never been colonized. The people of Afghanistan have always had friendly ties with the people of the United Subcontinent. However, the development of a new country called Pakistan was seen as both a threat and a way for the people of Afghanistan and India to become less connected to each other historically. The friendship pact of 1950 strengthened the relationship between India and Afghanistan. In fact, Afghanistan was the only country that voted against Pakistan’s membership in the UN. Pakistan and Afghanistan have a lot in common, including language, culture, and religion, but their relationship has not been strong. With its many-sided strategies, India has been trying to undermine Pakistan’s peace and security ever since it was formed. India’s plan to cut Pakistan off from its neighbors is a very bad sign for Pakistan. Pakistan is very worried about the Indian presence in Afghanistan because there are consulates in Kandahar and Jalalabad, which are close to the border between Pakistan and Afghanistan. The Afghan Taliban were very angry at Pakistan because of the US war on terror and Pakistan’s change in policy towards the Taliban.